2021
DOI: 10.1002/jmri.27635
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Evaluation of Repeatability and Robustness of Radiomic Descriptors in Healthy Brain Tissue Regions In Vivo Across Systematic Variations in T2‐Weighted Magnetic Resonance Imaging Acquisition Parameters

Abstract: Background Radiomic descriptors from magnetic resonance imaging (MRI) are promising for disease diagnosis and characterization but may be sensitive to differences in imaging parameters. Objective To evaluate the repeatability and robustness of radiomic descriptors within healthy brain tissue regions on prospectively acquired MRI scans; in a test–retest setting, under controlled systematic variations of MRI acquisition parameters, and after postprocessing. Study Type Prospective. Subjects Fifteen healthy partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…To date, MRI test-retest studies for the evaluation of repeatable and reproducible features, have been conducted through phantom research 15,28,[31][32][33] and by the use of MRI exams of healthy volunteers or cancer patients. 17,19,20,32,[34][35][36] None of these studies investigated feature repeatability and/or reproducibility in human breast MRI exams, and only one study investigated a breast phantom. 28 The study of Saint Martin et al 28 showed the necessity of image preprocessing dedicated to breast MRI exams before using features in further analysis.…”
Section: Discussionmentioning
confidence: 99%
“…To date, MRI test-retest studies for the evaluation of repeatable and reproducible features, have been conducted through phantom research 15,28,[31][32][33] and by the use of MRI exams of healthy volunteers or cancer patients. 17,19,20,32,[34][35][36] None of these studies investigated feature repeatability and/or reproducibility in human breast MRI exams, and only one study investigated a breast phantom. 28 The study of Saint Martin et al 28 showed the necessity of image preprocessing dedicated to breast MRI exams before using features in further analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Only specific subsets of radiomics features have been shown to be repeatable across readers 39,79,80 or implementations 71,81,82 . Parallel efforts in evaluating the reproducibility of radiomic features across controlled changes in echo time and repetition time in both phantom and in vivo settings also suggest that only a small subset of radiomic features are truly resilient to variations in acquisition settings 39,40,45,46,53 . Other than sources of image noise, a major factor impacting reproducibility and model generalizability is variations in image resolution, 83 where significant differences can reduce reproducible features to near zero 84 .…”
Section: Evaluating Repeatability and Reproducibility Of Image Quanti...mentioning
confidence: 99%
“…In radiomics, signal intensity values from contrast‐weighted MRI sequences (e.g., T 1 ‐weighted, T 2 ‐weighted, FLAIR, etc.) are often used to derive the texture features (Figure 4), but wide variations in acquisition settings such as echo/repetition times and flip angles between institutions, scanners, or body regions make a comparison of features derived from signal intensity values difficult or possibly even meaningless 39,40,43,45,53 . To address the variations in MR images, workflows therefore often include a variety of post‐processing steps 21,85,86 .…”
Section: Minimizing Variance In Image Quantitation Measurements For C...mentioning
confidence: 99%
See 2 more Smart Citations